2006
DOI: 10.1017/s002428290600569x
|View full text |Cite
|
Sign up to set email alerts
|

Synopsis of Usnea (lichenized Ascomycetes) from the Azores with additional information on the species in Macaronesia

Abstract: The genus Usnea is a conspicuous component of the macrolichen vegetation in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…Werth et al () suggested that hosts can create a selective environment for the lichenicolous T. lobariacearum because, despite their wide geographic distribution, the same parasite haplotypes consistently associate with a given host species. Host‐specific lineages within Biatoropsis all grow on hosts that have rather distinct morphological and chemical characteristics compared to the original hosts (Calvelo et al ; Clerc ), supporting speciation in sympatry. In particular, A2 evolved host specificity on a different genus ( Protousnea ) after a host switch.…”
Section: Discussionmentioning
confidence: 99%
“…Werth et al () suggested that hosts can create a selective environment for the lichenicolous T. lobariacearum because, despite their wide geographic distribution, the same parasite haplotypes consistently associate with a given host species. Host‐specific lineages within Biatoropsis all grow on hosts that have rather distinct morphological and chemical characteristics compared to the original hosts (Calvelo et al ; Clerc ), supporting speciation in sympatry. In particular, A2 evolved host specificity on a different genus ( Protousnea ) after a host switch.…”
Section: Discussionmentioning
confidence: 99%
“…Usnea aff. silesiaca is very similar to Usnea silesiaca (Clerc 1991(Clerc , 2006(Clerc , 2007 sharing the extended black pigment and anulate base, the CMA value and the morphology of branches and segments. Also the variation of soralia characteristics is in the range of U. silesiaca.…”
Section: Rinodina Obscuramentioning
confidence: 72%
“…As the last step, we combined the phylogenetic analysis with the phenotypic and chemical characters of the underlying samples using identification tools (Clerc 1987(Clerc , 2004(Clerc , 2006(Clerc , 2007Gerlach et al 2017Gerlach et al , 2019Gerlach et al , 2020Halonen 2000;Halonen et al 1998Halonen et al , 1999 ). Based on this approach, we arrived at the identifications presented and discussed below in the taxonomic section.…”
Section: Integrative Taxonomy and Comparison Of Methodsmentioning
confidence: 99%
“…A potential name for this material is Usnea columbiana Motyka ex Räsänen which, despite its name, was described from Chile (Räsänen 1936). According to Clerc (2006), this is a shrubby species producing soredia, with a black base and with a salazinic acid chemistry. We were able to confirm the morphology of the latter by checking a digital image of the lectotype on JSTOR Global Plants [https://plants.jstor.org/stable/viewer/10.5555/ al.ap.specimen.h9500229].…”
Section: Notesmentioning
confidence: 99%